2015
DOI: 10.1080/21645515.2015.1070996
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming barriers to HPV vaccination: A randomized clinical trial of a culturally-tailored, media intervention among African American girls

Abstract: Although genital HPV is the most prevalent STI in the US, rates of vaccination uptake among high-risk subgroups remain low. Investigations of vaccine compliance have mainly targeted mother-daughter dyads, which in some settings may prove difficult. This study examines an innovative culturally tailored, computer-delivered media-based strategy to promote HPV vaccine uptake. Data, inclusive of sociodemographics, sexual behaviors, knowledge, attitudes, and beliefs about HPV and vaccination were collected via ACASI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(88 citation statements)
references
References 42 publications
2
84
0
Order By: Relevance
“…An RCT evaluating an intervention targeting African-American females to increase HPV vaccine uptake (‘Girls on Guard’) found that only 12% of 216 participants initiated the vaccine course, with equal numbers in intervention and control groups 90. Another randomised study examined a computer-based health message intervention delivered in school-based clinics in a population of ethnically diverse parents of non-HPV vaccinated children (n=445) and found that rhetorical questioning message prompts increased vaccination intention, but not uptake 91…”
Section: Resultsmentioning
confidence: 99%
“…An RCT evaluating an intervention targeting African-American females to increase HPV vaccine uptake (‘Girls on Guard’) found that only 12% of 216 participants initiated the vaccine course, with equal numbers in intervention and control groups 90. Another randomised study examined a computer-based health message intervention delivered in school-based clinics in a population of ethnically diverse parents of non-HPV vaccinated children (n=445) and found that rhetorical questioning message prompts increased vaccination intention, but not uptake 91…”
Section: Resultsmentioning
confidence: 99%
“…Interventions have been described in research to aid in increasing the rate of vaccinating adolescents eligible to receive the HPV vaccine. Increasing availability of educational resources were implemented in several studies through the use of an interactive and age-appropriate information via electronics on an iPad, culturally-sensitive and accessible media interventions, and by providing education materials and patient reminders via telephone, text, or e-mail [13,[21][22][23][24].…”
Section: Interventions To Alter Hpv Vaccine Ratementioning
confidence: 99%
“…93 However, an intervention among university students comparing the impact of gain-or loss-framed video messages found no effect on vaccine behavior, 94 and a recent culturally tailored, computer-delivered, media-based strategy among African-American adolescent females within public health clinics increased vaccination, though rates were lower than the national average. 95 Research suggests that messages to promote HPV vaccine uptake should be tailored to age and should be culturally and linguistically appropriate. Specifically, messages that integrate a positive youth development framework and build on youths' assets, strengths, and protective factors are likely to be more effective than messages that seek to isolate HPV as a health concern.…”
Section: Skin Cancersmentioning
confidence: 99%